Ultrasound assessment of brain supplying arteries (transcranial) - Gröschel, Klaus; Harrer, Judith U.; Schminke, Ulf; Stegemann, Emilia; Allendörfer, Jens (Ultraschall in der Medizin - European Journal of Ultrasound, 2023)
Ultrasonography of intracranial arteries is a non-invasive and highly efficient method for the diagnosis and follow-up of patients with cerebrovascular diseases, also in the bedside setting of the critically ill. For reliable assessment and interpretation of sonographic findings, the technique requires – apart from dedicated anatomic and pathophysiological knowledge of cerebral arteries and their hemodynamics – the comprehension of alternative imaging modalities such as CT or MR angiography. This article reviews the transcranial color-coded duplex sonographic (TCCS) examination technique including the transcranial Doppler sonography (TCD) for a standardized ultrasound assessment of the intracranial arteries and typical pathological cases. As a complementary tool, transorbital ultrasound for the assessment of the optic nerve sheath diameter and adjacent structures is also described in this article.Die Sonografie der intrakraniellen Arterien ist eine nicht invasive und effektive Methode für die Diagnostik und Nachuntersuchung von Patienten mit zerebrovaskulären Erkrankungen, die auch als bettseitige Untersuchungsmethode auf der Schlaganfall- bzw. Intensivstation ihre Anwendung findet. Um eine verlässliche Untersuchung und Interpretation der sonografischen Befunde zu gewährleisten, ist – neben einer guten anatomischen und pathophysiologischen Kenntnis der hämodynamischen Zusammenhänge hirnversorgender Gefäße und deren Kollateralkreisläufe – auch eine erweiterte Kenntnis anderer bildgebender Modalitäten, wie z. B. der CT- oder MR-Angiografie, notwendig. Der vorliegende Artikel beschreibt die standardmäßige notwendige Untersuchungstechnik der transkraniellen farbkodierten Duplex- (TCCS) und Dopplersonografie (TCD) in der Darstellung intrakranieller Arterien sowie typische pathologische Fallkonstellationen. Als ergänzende Untersuchungsmethode wird die transorbitale Ultraschalluntersuchung, u. a. für die Bestimmung des Optikusnerv-Scheidendurchmessers und angrenzender Strukturen mit beschrieben.